1999
DOI: 10.1016/s0002-9378(99)70046-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous absorption of progesterone in postmenopausal women treated with transdermal estrogen

Abstract: OBJECTIVE:The objective of this study was to evaluate the serum levels of progesterone resulting from the application of a progesterone cream to the skin. STUDY DESIGN: Six postmenopausal women were evaluated at a university clinic over a 4-week period. RESULTS: Transdermal estradiol 0.05 mg was applied 2 days before the first application of progesterone (30 mg/d) and was continued throughout the study. Patches were changed twice a week. Progesterone cream was applied once a day for 2 weeks. On day 15 and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 16 publications
0
17
1
1
Order By: Relevance
“…In our study, significant increases from baseline were seen in both estradiol and progesterone levels after 12 weeks of treatment. Burry and colleagues suggested that by use of 30-60 mg of progesterone cream, luteal levels could be achieved [17]. The maximum median plasma progesterone level in our study of 2.5 nmol/l is far lower than that typically seen in the luteal phase of a premenopausal woman, and lower than levels achieved with standard doses of oral or vaginal progesterone.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In our study, significant increases from baseline were seen in both estradiol and progesterone levels after 12 weeks of treatment. Burry and colleagues suggested that by use of 30-60 mg of progesterone cream, luteal levels could be achieved [17]. The maximum median plasma progesterone level in our study of 2.5 nmol/l is far lower than that typically seen in the luteal phase of a premenopausal woman, and lower than levels achieved with standard doses of oral or vaginal progesterone.…”
Section: Discussioncontrasting
confidence: 57%
“…In a smaller study using 50 mg transdermal estrogen and 30-60 mg transdermal Progest 1 cream, a similar association between estradiol and progesterone levels was seen suggesting the possibility of similar mechanisms of absorption for both hormones [17].…”
Section: Discussionmentioning
confidence: 75%
“…This is consistent with reports from studies of other formulations of progesterone cream used for short durations, either with or without concomitant estrogen. [21][22][23][24][31][32][33] The effect of progesterone cream on progression of asymptomatic atherosclerosis was evaluated. Unadjusted results gave a mean (95% CI) increase in plaque thickness over the course of three years of 0.93 mm (0.3-1.6) in patients randomized to progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…Natural progesterone is well absorbed transdermally, avoids first‐pass hepatic metabolism and is relatively free from adverse effects [95] . The percutaneous application of progesterone cream could be a safe and effective route of administration [96] …”
Section: Novel Actions Of Progesteronementioning
confidence: 99%